Behavioural alterations induced by intermittent ethanol intake and noise exposure in adolescent rats. (4th April 2022) - Buján, Gustavo Ezequiel; D'Alessio, Luciana; Serra, Héctor Alejandro; Molina, Sonia Jazmín; Guelman, Laura Ruth
Abstract: Alcohol intake and exposure to noise are common activities of human adolescents performed in entertainment contexts worldwide that can induce behavioural disturbances. Therefore, the aim of the present work was to investigate in an experimental model of adolescent animals whether noise exposure and intermittent ethanol intake, when present individually or sequentially, might be able to modify different behaviours. Adolescent Wistar rats of both sexes were subjected to voluntary intermittent ethanol intake for 1 week followed by exposure to noise for 2 h and tested in a battery of behavioural tasks. Data show that males exposed to noise experienced a deficit in associative memory (AM), increase in anxiety‐like behaviours (ALB) and altered reaction to novelty (RN) when compared with sham animals, whereas females also showed an increase in risk assessment behaviours (RABs) and a decrease in exploratory activity (EA). In contrast, ethanol intake induced an increase in RAB and RN in males and females, whereas females also showed a deficit in AM and EA as well as an increase in ALB. When ethanol was ingested before noise exposure, most parameters were counteracted both in male and females, but differed among sexes. In consequence, it could be hypothesized that an environmental acute stressor like noise might trigger a behavioural counteracting induced by a previous repeated exposure to a chemical agent such as ethanol, leading to a compensation of a non‐adaptive behaviour and reaching a better adjustment to the environment. Abstract : Adolescent Wistar rats were subjected to either voluntary intermittent ethanol intake for 1 week, exposure to noise for 2 h or both and tested in a battery of behavioural tasks. It could be hypothesized that the presence of an environmental acute stressor such as noise might be enough to induce a behavioural counteracting of the changes observed after a repeated exposure to a chemical agent, leading to a compensation of a non‐adaptive behaviour to reach a better adjustment to the environment.